Synthesis of Cyclic α-Aminophosphonates through Copper-Catalyzed Enamine Activation - Han, Junbin; Paton, Robert S.; Xu, Bo; Hammond, Gerald B. (Synthesis, 2013)
A copper-catalyzed tandem-cyclization-triggered addition strategy that relies on electrophilic enamine activation has been used to synthesize various cyclic α-aminophosphonate derivatives in good to excellent yields. Both five- and six-membered rings can be generated under mild conditions with high regioselectivity. A mechanism based on copper-catalyzed enamine activation is proposed.
Keywords: copper; cyclic α-aminophosphonates; cyclization; enamines; hydroamination; nitrogen heterocycles; phosphorus